Integration and Role of Islamic Business Ethics in Mitigation of Financing Risks in Sharia Rural Bank (BPRS) In Indonesia - Siti Maghfiroh; Dwi Puspitasari; Lydiawaty binti Hassan Busry (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: The high rate of Non-Performing Financing (NPF) at Sharia rural banks (BPRS) in the last five years (2021-2025) reaching 10,36% in 2025, indicates that the technical and administrative risk management approaches implemented so far have not been fully effective in addressing the problem of problematic financing Methods: This study employed a qualitative approach, employing literature studies and analyzing secondary data published by the Financial Services Authority. Results: The findings indicate that Islamic Business Ethics (IBE) strengthens financing risk mitigation in BPRS through three main mechanisms: (1) preventing moral hazard by internalizing trust, honesty (ṣidq), and responsibility; (2) Strengthening Management and Employee Integrity and increasing contract transparency through clarity and fairness while avoiding gharar; and (3) Sharia-Based Risk Culture Formation and strengthening partnership-based relationships based on taʿāwun and distributive justice. Thus, IBE functions not only as a normative-ethical principle, but as a strategic and preventive behavioral risk control mechanism that complements conventional risk management and supports sustainable financing quality and institutional stability in BPRS. Conclusion and suggestion: BPRS needs to integrate Islamic Business Ethics values ​​more systematically into their financing risk management policies. Internalizing the values ​​of trustworthiness, honesty, and responsibility is not sufficient if outlined solely in a code of ethics; it needs to be reinforced with an ethics-based monitoring and performance evaluation system.